Measuring International Economic Linkages With Stock Market Data. - Ammer, John; Mei, Jianping (Journal of Finance, 1996)
This article develops a new framework for measuring financial and real economic linkages between countries. Using U.S. and U.K. data from 1957 to 1989, the authors find closer financial linkages after the Bretton Woods currency arrangement was abandoned and Britain suspended exchange controls. In a pairwise application to fifteen countries over a shorter period, they also find that news about future dividend growth is more highly correlated between countries than contemporaneous output measures. This suggests that there are lags in the international transmission of economic shocks and that contemporaneous output correlation may understate the magnitude of integration.